2002
DOI: 10.1080/02652030210123878
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants in organic and conventional foodstuffs in France

Abstract: The aim was to compare the levels of contamination in organic and conventional raw materials. To this end, the level of contamination by heavy metals (lead, cadmium, arsenic, mercury), nitrates and nitrites, and some mycotoxins were monitored. Fifteen products were tested in their organic and conventional forms, including meat, milk, eggs, vegetables and cereals. The median levels of contamination were calculated and compared with the recommended or regulated maximum levels. The maximum levels were exceeded fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 3 publications
6
73
3
3
Order By: Relevance
“…Several researches have presented higher trichothecene occurrence in traditional samples (Bernhoft, Clasen, Kristoffersen and Torp, 2010, Gottschalk, Barthel, Engelhardt, Bauer and Meyer, 2007, Edwards, 2009b, while others have shown higher contamination rates in organic samples (Malmauret, Parent-Massin, Hardy and Verger, 2002). In our case, despite the low number of organic samples that may have limited the results that were obtained, a higher incidence as well as higher contamination levels were observed in the conventional samples.…”
Section: Resultsmentioning
confidence: 37%
“…Several researches have presented higher trichothecene occurrence in traditional samples (Bernhoft, Clasen, Kristoffersen and Torp, 2010, Gottschalk, Barthel, Engelhardt, Bauer and Meyer, 2007, Edwards, 2009b, while others have shown higher contamination rates in organic samples (Malmauret, Parent-Massin, Hardy and Verger, 2002). In our case, despite the low number of organic samples that may have limited the results that were obtained, a higher incidence as well as higher contamination levels were observed in the conventional samples.…”
Section: Resultsmentioning
confidence: 37%
“…The same behavior is observed in previous studies on lead, cadmium and aflatoxins in the infant cereals (Hernández-Martínez, & Navarro-Blasco, 2012;. On the contrary, other reported studies suggest little difference in the arsenic content found in organic vegetables with respect to their ordinary or conventional production (Ghidini et al, 2005); only selective, occasional and sporadic contaminations may explain high levels of these contaminants (Malmauret, Parent-Massin, Hardy, & Verger, 2002).…”
Section: Influence Of Cereal Production Methods On Mercury and Arsenicmentioning
confidence: 38%
“…This indicated the importance of weather in late summer, as well as early summer on the final mycotoxin content of grain at harvest. Previous studies comparing organic to conventional wheat have either failed to identify significant differences between the two practices (Berleth 1998, Malmauret et al 2002, Cirillo et al 2003, Champeil et al 2004, Jestoi et al 2004 or have detected (Doll et al 2002, Schollenberger et al 2002, Schollenberger et al 2005 (Edwards, 2004). It is likely that these factors balance one another resulting in a similar concentration of DON in the two practices.…”
Section: (Insert Figure 1-5 Here)mentioning
confidence: 93%
“…Many studies failed to identify significant differences between the two practices within Europe (Malmauret et al 2002, Cirillo et al 2003, Champeil et al 2004, Jestoi et al 2004). However, significantly lower levels of DON in organic samples was detected in some regions of Germany (Doll et al 2002, Schollenberger et al 2002, Schollenberger et al 2005) although this was not the case in northern Germany in the mid-1990s (Berleth 1998).…”
Section: Introductionmentioning
confidence: 99%